Evaluation of Serum Levels of Carcinoembryonic Antigen in Allergic Bronchopulmonary Aspergillosis - Ono, Ryu; Moriyama, Gaku; Yamana, Kazunari; Mikami, Shintaro; Kyoyama, Hiroyuki; Noguchi, Toru; Yamamoto, Kazuo; Uematsu, Kazutsugu; Saito, Yuriko; Kobayashi, Takehito (Journal of Nippon Medical School, 2013)
Background: The serum level of carcinoembryonic antigen (CEA) is a marker of malignant disease but can also be increased in benign diseases. Patients with allergic bronchopulmonary aspergillosis (ABPA) have bronchial asthma showing a wide variety of radiological findings. We measured serum CEA levels in patients with ABPA and evaluated the relationships of serum CEA levels with peripheral blood eosinophil counts, total blood levels of immunoglobin (Ig) E, and findings of computed tomography (CT) in ABPA. Methods: The subjects were 13 patients (6 men and 7 women aged 34 to 76 years) who had been treated for ABPA at our hospital. Serum levels of CEA, peripheral blood eosinophil counts, total blood IgE levels, and CT findings were examined before and after treatment with prednisolone. Results: Before the start of the treatment 7 of 13 patients had serum CEA levels higher than the upper limit of normal. The serum CEA level was not correlated with eosinophil counts or total IgE values. Serum CEA levels were examined after treatment in 9 patients and were found to have significantly decreased as pulmonary consolidation improved. Furthermore, serum CEA levels before treatment in patients with pulmonary consolidation were significantly higher than those in patients without consolidation. Conclusion: Serum CEA levels are elevated in some patients with ABPA; these elevations might be associated with consolidation in the lung. Elevated serum CEA levels decrease as the consolidation decreases after treatment. The elevation of serum CEA might be attributed to the presence of local inflammation in the lung.